2018
DOI: 10.1017/jfm.2018.772
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of the self-sustaining cycle in separating and reattaching flows

Abstract: The separating and reattaching flows and the wake of a finite rectangular plate are studied by means of direct numerical simulation data. The large amount of information provided by the numerical approach is exploited here to address the multi-scale features of the flow and to assess the self-sustaining mechanisms that form the basis of the main unsteadinesses of the flows. We first analyse the statistically dominant flow structures by means of three-dimensional spatial correlation functions. The developed flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
78
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(100 citation statements)
references
References 46 publications
14
78
6
Order By: Relevance
“…the primary vortex; a secondary smaller counter-rotating vortex is formed around x = − 1.5, where no significant three-dimensional structures are observed. As already described in previous works (Cimarelli et al 2018a;Sasaki and Kiya 1991;Tenaud et al 2016), first at x ≈ −2 a Kelvin-Helmoltz like instability of the shear layer appears, leading to a breakdown into large-scale spanwise tubes. Further downstream, the spanwise tubes stretched by the mean flow roll up and originate hairpin-like vortices.…”
Section: Instantaneous Flowsupporting
confidence: 67%
See 1 more Smart Citation
“…the primary vortex; a secondary smaller counter-rotating vortex is formed around x = − 1.5, where no significant three-dimensional structures are observed. As already described in previous works (Cimarelli et al 2018a;Sasaki and Kiya 1991;Tenaud et al 2016), first at x ≈ −2 a Kelvin-Helmoltz like instability of the shear layer appears, leading to a breakdown into large-scale spanwise tubes. Further downstream, the spanwise tubes stretched by the mean flow roll up and originate hairpin-like vortices.…”
Section: Instantaneous Flowsupporting
confidence: 67%
“…In such scenario of highly scattered experimental and numerical information, a remarkable achievement was the recent first Direct Numerical Simulation (DNS) of the BARC flow in the turbulent regime. It was presented by Cimarelli et al (2018b), who employed the finitevolumes OpenFOAM toolbox (Weller et al 1998), and was then used in the derivative works (Cimarelli et al 2018a(Cimarelli et al , 2019. Albeit at a relatively low value of Re, these data represent a key step towards building a robust information set for the BARC flow, since DNS has the ability to remove from the picture the uncertainties related to turbulence modeling.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered here as an example of complex flow with two inhomogeneous directions and multiple separations and reattachments. Various flow structures are known to exist in different parts of the main recirculating bubble, and recently it has been suggested (Cimarelli et al 2018) that streamwise-and spanwise-oriented vortices populate the attached and detached portion respectively of the reverse boundary layer.…”
Section: Example: Separating and Reattaching Flowsmentioning
confidence: 99%
“…The snapshots used below for the AGKE analysis of the BARC flow are taken from the DNS study by Cimarelli et al (2018). Figure 10 visualises the mean and instantaneous velocity fields.…”
Section: Example: Separating and Reattaching Flowsmentioning
confidence: 99%
“…This factor alone, however, is not sufficient for a two-dimensionalization of the flow. Many research studies have in fact found the presence of spanwise-travelling structures and modes in similar 2-D extruded geometries, from bluff plates (Roshko 1993), extruded circular cylinders (Bearman 1992;Lehmkuhl et al 2013;Radi et al 2013;Rao et al 2013), and rectangular cylinders (Cimarelli, Leonforte & Angeli 2018), to D-shaped bodies (Parkin et al 2013), the latter being more representative of a vehicle shape. Here is where the second factor plays a major role in the, herein called, two-dimensionalization of the flow.…”
Section: The 2-d Versus 3-d Flow Topologiesmentioning
confidence: 99%